The General Strike as Crisis: Mapping a New Imaginary of the U.S. South and the Caribbean through Black Embodied Protest - McKinson, Kimberley D. (ACME, 2025)
Thinking with W.E.B. Du Bois’s elucidation of the General Strike, this essay is concerned with reading the Strike as constitutive of black embodied spatiotemporal crisis. In giving attention to Du Bois’s descriptions of the embodied and spatial pedagogies of the enslaved in the landscape of the U.S. South, I contend that it was through these pedagogies of protest that the General Strike both disrupted and suspended a Western linear ordering of time and geographical space. In re-mapping the General Strike as crisis through attention to black embodied praxis, I consider the political reverberations of the Strike in the Caribbean which I read through Jamaica’s Morant Bay Rebellion of 1865 and a Black Lives Matter protest in Kingston during the summer of 2020. In tracing the linkages between the General Strike, the Rebellion, and the protest, I disrupt the spatiotemporally familiar in order to propose a cartographic and epistemological shift predicated on situating the U.S. South and the Caribbean as an imaginary. This imaginary resists both territorialization and chronology and compels us to be attuned to the entanglement of black radical historical actors, landscapes, and embodied practices across spacetime.